Peran Guru Tahfidzul Qur’an dalam Meningkatkan Kualitas Hafalan Al-Qur’an pada Siswa di SD Takhasus Al-Qur’an Kalibeber Wonosobo - Arum Rizqi Aprilia; Fitrotul Hasanah; Istikomah Istikomah; Fathurrohman Fathurrohman (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to explain the role of Tafidzul Qur'an teachers in improving the quality of Al-Qur'an memorization among students at Takhasus Al-Qur'an Elementary School, Kalibeber, Wonosobo. The research method used is qualitative field and based on a case study approach. Data collection was carried out through observations and interviews related to Tafidzul Qur'an learning activities. The findings show that the role of Tafidzul Qur'an teachers is very important in motivating students, providing focused teaching, and creating a conducive learning environment. The quality of students' memorization of the Al-Qur'an at SD Takhasus Al-Qur'an Kalibeber Wonosobo has increased significantly thanks to the active role of Tafidzul Qur'an teachers and effective teaching methods. The implication of this research is the need to develop a Tafidzul Qur'an learning strategy that focuses on the role of the Tafidzul Qur'an teacher as the key to achieving optimal competency in memorizing the Al-Qur'an for students at the elementary level.